2009
DOI: 10.1136/tc.2009.031070
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of dual use of cigarettes and smokeless tobacco among US males: findings from national surveys

Abstract: BackgroundIn the USA, consumption of moist snuff continues to increase and cigarette manufacturers now control nearly its entire market. Manufacturers have developed new products that represent cigarette brand extension and in test marketing are promoting dual use of cigarettes and snuff. This study examined patterns of concurrent use of smokeless tobacco (ST) and cigarettes among young people and adults in the USA just before cigarette companies' control of the nation's ST market.MethodsData were drawn from f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
187
3
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(200 citation statements)
references
References 12 publications
9
187
3
1
Order By: Relevance
“…b User group was limited to those who used the product for the purpose of quitting cigarette smoking. (Bombard et al, 2007;Bombard et al, 2008;Richardson et al, 2012;Schuster et al, 2012;Tomar, 2010;Wetter et al, 2002). Interestingly, we found that those with lower incomes were more likely to use other smoked tobacco products or smokeless tobacco products for the purpose of cutting down on conventional cigarettes than were those with higher incomes.…”
Section: Notementioning
confidence: 48%
See 1 more Smart Citation
“…b User group was limited to those who used the product for the purpose of quitting cigarette smoking. (Bombard et al, 2007;Bombard et al, 2008;Richardson et al, 2012;Schuster et al, 2012;Tomar, 2010;Wetter et al, 2002). Interestingly, we found that those with lower incomes were more likely to use other smoked tobacco products or smokeless tobacco products for the purpose of cutting down on conventional cigarettes than were those with higher incomes.…”
Section: Notementioning
confidence: 48%
“…For example, Wetter et al (2002) found that, among adult smokers, those who used both cigarettes and smokeless tobacco were less likely to stop all tobacco use than were those who only used one product or the other. Tomar, Alpert, and Connolly (2010) found that unsuccessful attempts to quit smoking were more prevalent among males who used snuff than among those who did not. Zhu et al (2009) found no advantage in cessation for men who switched to smokeless tobacco.…”
Section: Introductionmentioning
confidence: 93%
“…14 The relatively higher prevalence of smokeless tobacco use among boys and non-Hispanic whites found in our study is consistent with reports in the literature. [15][16][17][18] In addition, the important .002…”
Section: Discussionmentioning
confidence: 99%
“…This is explained by the lower likelihood of women being dual cigarette and ST users than exclusive ST users and the higher likelihood of women being dual cigarette and ST users when compared to exclusive smokers. Research has demonstrated that dual- and multi-product tobacco users experience lower cessation rates [17,18], possibly due to greater cotinine and dependence levels [50]. On average, AN smokers living in Bristol Bay smoke about half as many cigarettes (7.8) per day [42] as US smokers (14.2) [51], but demonstrate similar plasma cotinine levels (170 ng/mL and 200 ng/mL, respectively), suggesting altered nicotine metabolism [49,52].…”
Section: Discussionmentioning
confidence: 99%